Evaluasi Simpang Bersinyal Taman Sari – Cikapayang Kota Bandung Dengan Analisis VisSim - Hutahaean, Yopi Grace; Susilo, Budi Hartanto (Jurnal Teknik Sipil, 2021)
Taman Sari - Cikapayang intersection is one of the intersections in Bandung that has traffic problems, namely traffic jams. It can be seen from the length of the long lines at the arms of the Taman Sari - Cikapayang intersection to the Sulanjana intersection which often occurs during rush hour and weekend. Traffic jam occur in the Taman Sari - Cikapayang intersection during weekend because of the large number of cars parked along the Cikapayang road and the front of ??Balubur Town Square (Baltos) area. To minimize the level of congestion at the Taman Sari - Cikapayang intersection, a study was conducted to determine the causes of congestion at the Taman Sari - Cikapayang intersection and optimize the performance of the Taman Sari - Cikapayang intersection. It could be maked by modeling the Intersection using VisSim software. From the results of modeling conducted on VisSim software to describe congestion in the area of ??Baltos can be obtained an alternative solution to optimize the performance of Taman Sari – Cikapayang intrrsection. The results of the evaluation of traffic performance at Simpang Taman Sari - Cikapayang is obtained by the length of the largest queue at rush hour in the afternoon are found in the Cikapayang approach with a length of 353 meters with a LoS F. Based on simulation, the best solution to solve the problem of the length of the queue and LoS in the Baltos area is by banned the parking area on the Baltos area because it can reduce the length of the existing condition queue on the Taman Sari and Cikapayang and can increase LoS F in existing conditions to LoS A.